Practical teaching skills for driving instructors develop and improve you teaching, training and coaching skills. - Miller, John, 1938 December 29- (Kogan Page, 2009)
Written for both existing and trainee driving instructors, Practical Teaching Skills for Driving Instructors shows how to develop and improve the ability to teach driving as a lifetime skill. The companion title to the popular best-selller The Driving Instructor's Handbook, it offers advice on teaching, communication and coaching skills. Fully revised, it investigates how and why people learn and the different teaching and learning processes involved. With sections on structuring a lesson and problem solving, it also looks at the reasons why people learn to drive and the motivation involved in.